PERAN PERPUSTAKAAN DALAM MENGEMBANGKAN LITERASI DAN PENGETAHUAN MASYARAKAT - Rohmaniyah, Rohmaniyah; Sari, Kartika (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Libraries have a crucial role in developing community literacy and knowledge. As a center for information and learning, libraries provide access to a variety of diverse information resources, both in physical and digital form. With collections of books, journals, magazines and electronic databases, libraries offer opportunities for the public to expand their knowledge in various fields of science. The library also functions as a place for lifelong learning. Educational programs such as workshops, seminars and courses organized by libraries help improve people's literacy skills and technical knowledge. In addition, libraries are often centers of cultural and social activities that can raise awareness of local and global issues. In the context of literacy, libraries play an important role in developing reading and writing skills. The various literacy programs offered, such as book clubs and storytelling sessions, encourage an interest in reading from an early age. Apart from that, libraries also play a role in reducing information gaps in society. By providing free or low-cost access to information, libraries help address inequalities in access to knowledge.